2019
DOI: 10.3802/jgo.2019.30.e94
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of immunotherapy in advanced/recurrent female genital tract melanoma: a preliminary experience

Abstract: Objectiveimmunotherapy with immune checkpoint inhibitors has become one of the standard therapeutic modalities for patients with advanced melanoma. Melanoma of the female lower genital tract is a rare and aggressive disease, with poor long-term clinical outcomes. To date, no study evaluated the role of immunotherapy in metastatic melanoma of the lower genital tract.MethodsData of women with metastatic melanoma of the lower genital tract were prospectively collected. Survival outcomes over time was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
(42 reference statements)
0
25
1
Order By: Relevance
“…Female genitourinary tract melanomas account for 3% of all melanomas [ 75 ]. The vulva is the most frequent site involved (70%), followed by the vagina and, more rarely, the cervix [ 76 ]. Although genital melanomas can occur at any age, a mean age at diagnosis of 60 years has been reported [ 77 , 78 ].…”
Section: Mucosal Melanomas At Uncommon Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Female genitourinary tract melanomas account for 3% of all melanomas [ 75 ]. The vulva is the most frequent site involved (70%), followed by the vagina and, more rarely, the cervix [ 76 ]. Although genital melanomas can occur at any age, a mean age at diagnosis of 60 years has been reported [ 77 , 78 ].…”
Section: Mucosal Melanomas At Uncommon Sitesmentioning
confidence: 99%
“…The available data mainly consist of small retrospective series and support the use of immunotherapy in improving survival. Indini et al (2019), in a single center experience including seven female lower genital tract melanomas, reported a poor response rate for immunotherapy (28.5%) [ 76 ]. A better progression-free survival and overall survival was observed in patients under anti-PD-1 therapy compared to those receiving anti-CTLA4 ( p = 0.01 and p = 0.15, respectively) [ 76 ].…”
Section: Mucosal Melanomas At Uncommon Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 13 patients with VVM receiving immune checkpoint inhibitors were identified from previously published cases in the literature 15 20 ; 10 patients with metastatic or unresectable VVM were included (see Table 3 ); 3 patients, who received neoadjuvant ipilimumab and radiation and subsequently underwent surgery, were not included. 20 The best overall ORR with immune checkpoint inhibitors in the combined cohort of the 23 patients was 30.4% (95% CI = 11.6%–49.2%), and the CBR was 52.2% (95% CI = 31.8%–72.6%).…”
Section: Resultsmentioning
confidence: 99%
“…This study included a total of 35 mucosal melanomas, 14 of which vulvovaginal. A small retrospective study of patients with metastatic melanoma of the lower genital tract from Italy showed that the response rate to immunotherapy was 28.5% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%